Malignant Leydig cell tumor in dogs: two cases and a review of the literature. (July 2019) - Kudo, Tomoo; Kamiie, Junichi; Aihara, Naoyuki; Doi, Masaki; Sumi, Ayumi; Omachi, Tetsuo; Shirota, Kinji
Malignant Leydig cell tumor (MLCT) is a rare testicular tumor in dogs. We report herein 2 dogs with MLCT and cutaneous metastasis. Grossly, marked enlargement and distortion of the involved testes were noted; on cut surface, the parenchyma was completely replaced by neoplastic tissue. In addition, these tumors had extensive necrosis and hemorrhage. Case 1 had a rapidly growing cutaneous mass in the left angle of the mouth; the lesion was well-circumscribed and had an indistinct lobular pattern. Case 2 had multiple cutaneous masses in the dorsal neck region, the thoracic back region, and the right hindlimb. Microscopically, the tumor lobules were composed of oval-to-polyhedral cells with eosinophilic cytoplasm and resembled testicular tumors. By immunohistochemistry, the neoplastic cells in both the testicular and cutaneous tumors were positive for inhibin-alpha and melan A. The mitotic counts of the primary tumors from cases 1 and 2 were 21 and 11 per 10 high-power fields, respectively. Based on these findings, the cases were diagnosed as MLCT with cutaneous metastasis. Ki-67 expression in the neoplastic cells of the 2 cases was higher than in benign Leydig cell tumors. Our findings may be helpful for the diagnosis of canine MLCT.